A brief review of Cn-symmetric calixarenes and resorcinarenes - Mcildowie, Matthew; Mocerino, Mauro; Ogden, Mark (Taylor and Francis Ltd, 2010)
Calixarene and resorcinarene macrocycles are renowned for their ability to form inclusion complexes or act as molecular scaffolds. The addition of chirality to these non-planar molecules is an exciting enhancement of their already robust potential, offering much promise as ligands for chiral catalysis and enantioselective separations. Chiral calixarenes can be produced by the attachment of a chiral moiety or by the placement of an achiral functionality on the macrocyclic structure so as to render it asymmetric. The latter method is particularly intriguing, often resulting in molecules which have Cn dissymmetry. This review describes examples of the Cn-dissymmetric calixarenes and resorcinarenes prepared to date and discusses aspects of their chirality, including their pictorial and written descriptors.